A randomized phase II trial of Captem or Folfiri as second-line therapy in neuroendocrine carcinomas - Bongiovanni, Alberto; Liverani, Chiara; Foca, Flavia; Bergamo, Francesca; Leo, Silvana; Pusceddu, Sara; Gelsomino, Fabio; Brizzi, Maria Pia; Di Meglio, Giovanni; Spada, Francesca; Tamberi, Stefano; Lolli, Ivan; et al. (European journal of cancer (1990), 2024)
Neuroendocrine Carcinomas (NECs) prognosis is poor.No standard second-line therapy is currently recognized after failure of platinum-based first-line treatment. FOLFIRI and CAPTEM regimens have shown promising activity in preliminary studies. We aimed to evaluate these regimens in metastatic NEC patients. This is an open-label, multicenter, randomized non-comparative phase II trial to evaluate the activity and safety of FOLFIRI or CAPTEM in metastatic NEC patients. Primary endpoints were the 12 weeks-Disease Control Rate (12w-DCR) by investigator assessment per RECIST v1.1 and safety per CTCAE v5.0. Additional endpoints included overall response rate (ORR), progression-free survival (PFS) and overall survival (OS). Patients’ serum samples were subject to NGS miRNome profiling in comparison with healthy donors to reveal differentially expressed miRNAs as candidate circulating biomarkers. The study was halted for futility at interim analysis, as the minimum 12w-DCR threshold of 10 out of 25 patients required for the first step was not reached. From 06/03/2017 to 18/01/2021, 53 out of 112 patients were enrolled. Median follow-up was 22.6 months (range: 1.4–60.4). The 12w-DCR was 39.1 % in the FOLFIRI arm and 28.0 % in the CAPTEM arm. In the FOLFIRI subgroup the 12-months OS rate was 28.4 % (95 % CI: 12.7–46.5) while in the CAPTEM subgroup it was 32.4 % (95 % CI: 14.9–51.3). The most common G3-G4 side effects were neutropenia (n = 5, 18.5 %) and anemia (n = 2, 7.4 %) for FOLFIRI and G3-G4 thrombocytopenia (n = 2, 8.0 %), G4 nausea/vomiting (n = 1, 4.0 %) for CAPTEM. Three microRNAs emerged as NEC independent predictors. High expression values were found to be significantly associated with decreased PFS and OS. The safety profile of FOLFIRI and CAPTEM was manageable. FOLFIRI and CAPTEM chemotherapy showed comparable activity in the second-line setting after progression on etoposide/platinum. NCT03387592 •No second-line treatment recognized for NEC patients after platinum-based therapy.•This phase II trial investigates activity and safety of second-line treatments in NEC.•FOLFIRI and CAPTEM in second-line setting improve the quality of life of NEC patients.•FOLFIRI or CAPTEM might be used interchangeably accordingly to, comorbidities and toxicity profile.•miR-1246, miR-1290 and miR-320c are NEC independent prognostic predictors.